Diminished citizenship in the era of mass incarceration - Sered, Susan Starr (Punishment & society, 2021)
This paper lays out a model of diminished citizenship as a tool for understanding the experiences of the large population of people who, at least in part by virtue of their relations with criminal justice apparatuses, do not benefit from the full complement of responsibilities and rights associated with citizenship in a modern democracy. The frame of diminished citizenship places mass incarceration within a larger historical and social context, moving ideas about “criminals” away from the individual focus of mainstream criminology and providing a useful framework for considering how a variety of marginalized groups navigate the American landscape. At the same time, the frame of mass incarceration offers insights into a crucial mechanism for constructing, diminishing and enforcing citizenship in the United States. Our argument draws on our decade-long ethnographic research with a cohort of women who had been released from prison in Massachusetts in 2007–2008.